2022
DOI: 10.1002/jcp.30705
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between ERK and MRTF‐A signaling regulates TGFβ1‐induced epithelial‐mesenchymal transition

Abstract: Epithelial-mesenchymal transition (EMT) is a physiological process that is essential during embryogenesis and wound healing and also contributes to pathologies including fibrosis and cancer. EMT is characterized by marked gene expression changes, loss of cell-cell contacts, remodeling of the cytoskeleton, and acquisition of enhanced motility. In the late stages of EMT, cells can exhibit myofibroblast-like properties with enhanced expression of the mesenchymal protein marker α-smooth muscle actin and contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Important mediators include the dysregulated release of matrix metalloproteinases during the inflammatory phase of ARDS, which causes epithelial and endothelial injury and unchecked fibroproliferation 45 (Figure 4 A,B). Canonical profibrotic pathways regulated by TGF‐β are important, and there is evidence that vascular dysfunction is a key component of the switch from ARDS to fibrosis, with VEGF and cytokines such as interleukin 6 (IL‐6) and TNF‐α implicated 46,47 . It remains unclear why certain individuals could recover from such an insult, whereas in others there is a shift to unchecked cellular proliferation with the accumulation of fibroblasts and myofibroblasts and the excessive deposition of collagen alongside other components of the ECM to result in progressive pulmonary fibrosis.…”
Section: Roles Of Tcs Mediated Cell Communication In Pulmonary Fibros...mentioning
confidence: 99%
“…Important mediators include the dysregulated release of matrix metalloproteinases during the inflammatory phase of ARDS, which causes epithelial and endothelial injury and unchecked fibroproliferation 45 (Figure 4 A,B). Canonical profibrotic pathways regulated by TGF‐β are important, and there is evidence that vascular dysfunction is a key component of the switch from ARDS to fibrosis, with VEGF and cytokines such as interleukin 6 (IL‐6) and TNF‐α implicated 46,47 . It remains unclear why certain individuals could recover from such an insult, whereas in others there is a shift to unchecked cellular proliferation with the accumulation of fibroblasts and myofibroblasts and the excessive deposition of collagen alongside other components of the ECM to result in progressive pulmonary fibrosis.…”
Section: Roles Of Tcs Mediated Cell Communication In Pulmonary Fibros...mentioning
confidence: 99%
“…It has recently been reported that inhibition of ERK phosphorylation increases focal adhesion, cell contractility and alteration in expression of genes correlated to EMT induced by TGF- β1. Subcellular localization and phosphorylation of myocardin-related transcription factor-A (MRTF-A) is a suggested mediator which indicates a crosstalk between ERK and MRTF-A signaling in EMT promotion [ 92 ]. Figure 1 demonstrates the mentioned molecular mediators which lead to EMT promotion.…”
Section: A Review On Recent Findings Of Epithelial-to-mesenchymal Tra...mentioning
confidence: 99%
“…27 It has recently been shown that specific blockade of ERK inhibits EMT, including that in TGF-β-treated mammary epithelial cells, mainly by sequestering MRTF-A in cytoplasm. 28 While EMT is regulated by TGF-β, local oxidative stress enhances its fibrotic effects. 29 In the presence of reactive oxygen species, activity of the RhoA/Rac1 signaling pathway is significantly increased following activation by TGF-β.…”
Section: Role Of Srf/mrtf-a In Fibrosismentioning
confidence: 99%
“…One of the key factors exerting EMT is TGF‐β, which induces a multitude of signaling pathways, especially extracellular signal‐regulated kinase (ERK) 27 . It has recently been shown that specific blockade of ERK inhibits EMT, including that in TGF‐β‐treated mammary epithelial cells, mainly by sequestering MRTF‐A in cytoplasm 28 . While EMT is regulated by TGF‐β, local oxidative stress enhances its fibrotic effects 29 .…”
Section: Role Of Srf/mrtf‐a In Fibrosismentioning
confidence: 99%